The Application of Digital Leadership of Subdistrict Head on Public Service Performance with the Delegation of Regent/Mayor Authorities as the Moderating Variable - Dwi Mardiana (Universitas Airlangga, 2020)
The low Human Development Index (HDI) for the protected areas is a government-focused development priority, especially in the health sector. Attempts should be made to enhance the efficiency of regional public services related to efforts to break the chain of Covid-19. Subdistrict heads have also contributed greatly to the optimization of task assignments to the apparatus. An appeal to implement social distancing becomes an obstacle for the subdistrict head for there is no face-to-face meeting with the assigned apparatus. The subdistrict heads are required to be able to adapt to the situation. Thus, the subdistrict heads must use digital media in carrying out their duties. The leadership style that influences service performance and is appropriate to be implemented in this phenomenon is digital leadership. Meanwhile, the delegation of authority is a variable that might strengthen the influence of leadership on the performance of public services. This study aims to investigate the effect of the subdistrict head’s digital leadership on the performance of public service employees in the subdistricts of Pendalungan with the delegation of regent/mayor authority as a moderating variable.